Development of Live Worksheets Based on Problem-Based Learning to Improve Science Critical Thinking Skills - Fitri Kartika Sari; Aldina Eka Andriani (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Optimizing the use of student worksheets in science learning is a strategic effort to improve the quality of the learning process and foster students' critical thinking skills. This study aims to describe the design, determine the feasibility, and examine the effectiveness of Live Worksheets based on Problem Based Learning in improving the critical thinking skills of fifth-grade students at SD Negeri Jatibarang 03 on the topic of the human respiratory system in improving the critical thinking skills of fifth-grade students at SD Negeri Jatibarang 03 on the topic of the human respiratory system. This research employed a Research & Development (R&D) method using the ADDIE development model, which consists of analyze, design, development, implementation, and evaluation stages. The research subjects were 20 fifth-grade students. Data collection techniques included tests (pre-test and post-test) and non-test methods such as observation, interviews, questionnaires, and documentation. Data were analyzed qualitatively and quantitatively using normality tests, paired sample t-tests, and N-gain analysis. The Live Worksheets based on Problem-Based Learning were developed in Canva and accessed through the Live Worksheets platform. The product consists of a cover page, group identity page, general information page, core learning materials with problem-based questions, and a final page containing reinforcement materials and developer profiles. The feasibility results indicated very feasible criteria, with validation percentages of 92% from material experts and 94% from media experts, and positive responses from 90% of teachers and students. The effectiveness results showed a significant increase in scores from 47.5 to 71.25, a Sig. (2-tailed) value of 0.000 < 0.05, a 22% improvement in critical thinking skills, and an N-gain of 0.4741 (moderate category). Thus, the Live Worksheets based on Problem-Based Learning were deemed successfully developed, feasible, and effective in improving students' critical thinking skills in science.